Memorial stone in front of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
These memorial stones are found in an open space in front of the Mandaleshwar Mahadev Temple. Below the depiction of the human figure, there are a few inscription lines. The inscription is in the Sanskrit language and Devanagari script.